A comparative study of energy partioning of Tra Catfish (Pangasius hypophthalmus) fed farm-made feed and commercial feed - Tran Le Cam Tu; Yakupitiyage, Amararatne; Gallardo, Wenresti G.; Thakur, Dhirendra Prasad; Bhujel, Ram C.; Nguyen Thanh Phuong; Sweden (Sida) (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
This research was conducted to evaluate the energy budget (C, P, F, R, and U) of juvenile (20g) Tra catfish (Pangasius hypophthalmus) fed with two different dietary treatments i.e. moist farm-made feed (FMF) and dry commercial feed (Pellet). There were three different experiments conducted at 30o C. First, a growth experiment was conducted for 50 days, using 288 fish randomly placed in the eight 500L tanks. Fish were fed two times per day and the parameters such as energy intake (C), nitrogen intake (CN), recovered energy (P), and retained nitrogen (PN) were gathered. Second, digestibility experiment using 192 fish placed in eight 170L fecal settlement tanks. Fish were fed with the same feeds but added 1% chromic oxide. Fish were fed until satiation one time per day for seven days. Faecal samples were collected for three consecutive days and pooled. Experimental feeds and feces were analyzed for chromic oxide, gross energy and crude protein. Third, the oxygen consumption of twenty healthy and active starved fish per treatment was measured in a flow-through respirometer, to estimate standard and active metabolism (RS and RA, respectively). Urinary and gill loss of N was estimated from the difference between the nitrogen between intake and expenditure. The amount of energy lost as heat (R) was indirectly computed by the difference between energy intake and retained. The result showed that energy budget of Tra fish can be expressed as 100C = 36.8P + 4.90U + 29.7F + (10.5RS + 7.92RA + 10.6RF) for FMF and 100C = 46.3P + 3.62U + 16.5F + (9.42RS + 7.42RA + 16.8RF) for commercial pelleted feed. Despite the significantly different quantity of food intake between treatments, the daily dietary energy intake of Tra catfish (~20g) is approximately the same (565-605 J/g) for both feed types and the maintenance energy requirement per day is about 101 J/g. However, fecal and excretory energy losses for fish fed FMF were significantly (p < 0.05) higher than that of fish fed commercial pellets. As a result, 20g-Tra catfish fed FMF and commercial pellet retained 4.07 and 5.59 KJ 0f energy, respectively.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Aquaculture and Aquatic Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2010
Keywords: Catfishes -- Feeding and feeds; Bioenergetics